2019
DOI: 10.1111/cogs.12770
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Offloading: Structuring the Environment to Improve Children's Working Memory Task Performance

Abstract: Research has shown that adults can engage in cognitive offloading, whereby internal processes are offloaded onto the environment to help task performance. Here, we investigate an application of this approach with children, in particular children with poor working memory. Participants were required to remember and recall sequences of colors by placing colored blocks in the correct serial order. In one condition the blocks were arranged to facilitate cognitive offloading (i.e., grouped by color), whereas in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 69 publications
0
20
2
Order By: Relevance
“…Despite being a central facet of complex human behaviour, the developmental origins of cognitive offloading remain largely unexamined. Previous studies have shown that young children can enhance internal cognitive performance with behaviours such as finger-counting [41] and by questioning knowledgeable adults in situations of uncertainty [42], and also that they can benefit from cognitive offloading cues provided by an experimenter [43][44][45]. Yet, the critical question of when and how humans begin to selectively modify their environment to overcome internal cognitive shortcomings remains unanswered [46].…”
Section: Introductionmentioning
confidence: 99%
“…Despite being a central facet of complex human behaviour, the developmental origins of cognitive offloading remain largely unexamined. Previous studies have shown that young children can enhance internal cognitive performance with behaviours such as finger-counting [41] and by questioning knowledgeable adults in situations of uncertainty [42], and also that they can benefit from cognitive offloading cues provided by an experimenter [43][44][45]. Yet, the critical question of when and how humans begin to selectively modify their environment to overcome internal cognitive shortcomings remains unanswered [46].…”
Section: Introductionmentioning
confidence: 99%
“…Though recent research has found evidence consistent with the notion that individuals make spatial decisions that lead to improvements in task performance, there is also evidence that efficient task performance is not the only factor at play. For instance, Berry et al (2019) found that even though school‐age children recognize that organizing colored blocks in their task space (i.e., by color categories) makes performing a subsequent spatial working memory task easier, they do not necessarily opt to rearrange their space when provided with the opportunity to do so. In a similar vein, Zhu and Risko (2016) found that the tendency to place objects in positions that facilitated task performance depended on the physical effort required to reach for these objects.…”
Section: That's My Spot! Examining Spatial Habit Formation In a Naturalistic Settingmentioning
confidence: 99%
“…This discrepancy between the potential benefits of spatial organisation and the lack of engagement in organisational activity was further demonstrated in a series of studies involving school-age children (Berry et al, 2019).…”
Section: Introductionmentioning
confidence: 99%